1990
DOI: 10.1002/ajmg.1320370122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence study of Prader‐Willi syndrome in North Dakota

Abstract: A prevalence study of Prader-Willi syndrome (PWS) has been conducted in North Dakota. All pediatricians, neurologists, child psychiatrists, psychologists, and clinical geneticists were surveyed. The state's comprehensive evaluation center, the state hospital, the state institution for the mentally retarded, and group homes for the developmentally disabled, including one for persons with PWS, were also contacted. Seventeen patients were identified, 8 males, 8 females, and one patient whose sex was not specified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 5 publications
1
46
0
Order By: Relevance
“…The myth that gonadal replacement may lead to a more aggressive behaviour and aggravate temper tantrums was not confirmed by our observations. Though the number of patients examined was limited due to the rarity of the syndrome (prevalence 1:15,000–25,000) [44, 45], a more generalized early treatment of hypogonadism in PWS is justified to examine prospectively the androgenic effects on behaviour in larger controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…The myth that gonadal replacement may lead to a more aggressive behaviour and aggravate temper tantrums was not confirmed by our observations. Though the number of patients examined was limited due to the rarity of the syndrome (prevalence 1:15,000–25,000) [44, 45], a more generalized early treatment of hypogonadism in PWS is justified to examine prospectively the androgenic effects on behaviour in larger controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated to have an incidence of 1:16,000 [1]. Common features include hypotonia and feeding difficulties in infancy, hyperphagia with early childhood obesity, short stature, hypogonadism, mental retardation with behavioral abnormalities, small hands and feet, excessive daytime sleepiness, and temperature instability [2].…”
Section: Introductionmentioning
confidence: 99%
“…8 Most authors estimate the prevalence based on clinical diagnoses within a small population (less than 265 000) and a limited age group (under 30 years). 8 -10 A recent study including all ages, 11 found a birth incidence of 1:29 000, a prevalence of 1:52 000 and a mortality rate of 3% a year across all ages and 7% a year in those over 30 years of age.…”
Section: Introductionmentioning
confidence: 99%